Corrosion-resistant composite wave-absorbing material and preparation method thereof
By combining hydrofluoric acid modified graphene with coupling agent modified sheet carbonyl iron to form a low dielectric fluorinated graphene clad layer, the composite absorbing materials have solved the problems of narrow frequency bands, large density, poor stability and limited corrosion resistance in the composite absorbing materials, and achieved efficient absorbing performance and significant corrosion resistance.
Patent Information
- Application Number
- CN202411846054.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-25
AI Technical Summary
The existing composite absorbing materials have shortcomings in the problems of narrow frequency bands, large density, poor stability and limited corrosion resistance, especially in the case of long-term use.
By combining hydrofluoric acid modified graphene with coupling agent modified sheet carbonyl iron to form a low dielectric fluorinated graphene coating, the corrosion resistance of carbonyl iron and the impedance matching performance of composite materials are improved while maintaining excellent wave absorption properties.
The corrosion resistance of carbonyl iron and the impedance matching performance of composite materials are significantly improved, while maintaining efficient wave absorption performance. When the coating thickness is 3mm, its reflection loss peak can reach -35.5db.
Smart Images

Figure CN119505807A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of absorbing materials, and in particular relates to a corrosion-resistant composite absorbing material and a preparation method thereof. Background Art
[0002] Absorbing materials refer to materials that can absorb electromagnetic waves. They have been widely used in both military and civilian fields. In the civilian field, they can promote the research and large-scale use of mobile communications. In the military field, they can improve the development of stealth technology and the practical application of weapons and equipment. However, with the improvement of technical requirements, traditional absorbing materials can no longer meet the diversified needs of the field. In addition to having a high absorption rate of electromagnetic waves in a wider frequency band, absorbing materials should also have good mechanical properties, weather resistance, and corrosion resistance.
[0003] Carbonyl iron has become a commonly used magnetic wave absorbing material due to its advantages of high saturation magnetization, Curie temperature and large magnetic loss angle. The flake carbonyl iron obtained by further controlling its morphology has the characteristics of high dielectric and high magnetic permeability, which helps to break through the Snoek limit. In addition, the dielectric of carbonyl iron can be controlled by morphology control and surface modification. However, the use of carbonyl iron alone often leads to problems such as high density, poor stability and narrow absorption band.
[0004] Graphene is a two-dimensional material with excellent electromagnetic properties and good chemical stability and barrier properties. It has the characteristics of nonlinear response to frequency radiation and has a certain electrical loss capacity. Therefore, it often appears in the research and application of the field of wave absorption in combination with carbonyl iron. For example, Chinese patent CN 109897597 B discloses a corrosion-resistant carbonyl iron / graphene composite wave absorbing material for 5G mobile communication frequency band, which improves the impedance matching and wave absorbing performance of the wave absorbing material by adding graphene to carbonyl iron; and improves the corrosion resistance of the composite wave absorbing material by bluing the material. However, the heat treatment bluing process requires strict control of process parameters, regular inspection and maintenance of equipment, and relatively high production requirements; and the corrosion resistance of the blue film alone is still limited, especially the corrosion resistance will degrade under long-term use, and usually it needs to be treated by oiling or waxing to further improve the corrosion resistance of the material. In addition, existing composite absorbing materials still have problems such as large dielectric constant and poor impedance matching. Therefore, in order to obtain composite absorbing materials that are easy to prepare, have good absorbing properties and excellent long-term corrosion resistance, further improvements to related processes are needed. Summary of the invention
[0005] In view of the above-mentioned problems, the present invention aims to provide a corrosion-resistant composite absorbing material and a preparation method thereof. Graphene modified with hydrofluoric acid is composited with flaky carbonyl iron modified with a coupling agent to form a low dielectric fluorinated graphene coating on the surface of the carbonyl iron, thereby improving the corrosion resistance of the carbonyl iron and the impedance matching performance of the composite material, while also enabling the composite material to maintain excellent absorbing performance.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a corrosion-resistant composite absorbing material comprises the following steps:
[0007] 1) adding hydrofluoric acid to the graphene aqueous dispersion, hydrothermally reacting, cooling, filtering, and washing to neutrality to obtain modified graphene;
[0008] 2) mixing the carbonyl iron powder with an organic solvent, ball milling, and drying to obtain flaky carbonyl iron powder;
[0009] 3) Dispersing the flaky carbonyl iron powder in an organic solvent under stirring, adding a coupling agent and water, continuously stirring, then adding the modified graphene dispersion, heating in an oil bath, filtering, and drying to obtain a composite absorbing material.
[0010] Furthermore, in step 1), the graphene concentration in the graphene aqueous dispersion is 0.01-0.1 g / mL, the solid-liquid ratio of graphene to hydrofluoric acid is 1-20 g / 5-60 mL, and the mass concentration of hydrofluoric acid is 10%-48%.
[0011] Furthermore, in step 1), the hydrothermal reaction temperature is 220-280° C. and the insulation time is 4-16 hours.
[0012] Furthermore, in step 2), the organic solvent is anhydrous ethanol, the ball-to-material ratio during ball milling is 20-100:1, the ball milling speed is 800-1200 rpm, and the ball milling time is 12-48 h; the drying temperature is 60-80° C., and the drying time is 0.5-4 h.
[0013] Furthermore, in step 3), the organic solvent is one or more of anhydrous ethanol and ethylene glycol; the coupling agent is KH-550, the mass ratio of flaky carbonyl iron powder, coupling agent and water is 100:0.1~1:1~10, the continuous stirring speed is 800~1200rpm, and the stirring time is 1~4h.
[0014] Furthermore, in step 3), the solid content of the modified graphene dispersion is 3% to 10%, and the mass ratio of the flaky carbonyl iron powder to the modified graphene in the mixed dispersion is 100:2 to 10.
[0015] Furthermore, in step 3), the oil bath temperature is 60-100° C. and the oil bath time is 1-6 h.
[0016] When the corrosion-resistant composite absorbing material is prepared by the above preparation method, the surface of the graphene modified by hydrofluoric acid carries a large amount of -COOH, and the surface of the flaky carbonyl iron powder modified by the coupling agent KH-550 carries a large amount of -NH2. The modified flaky carbonyl iron powder is chemically bonded to the graphene with -COOH on the surface through the -NH2 on its surface, that is, a core is formed of flaky carbonyl iron powder, and the shell structure is a coated core-shell structure of ductile graphene. This forms a low-dielectric fluorinated graphene coating layer on the surface of the flaky carbonyl iron, which can significantly improve the corrosion resistance of the carbonyl iron and improve the impedance matching performance of the composite material. When the coating thickness is 2mm, its reflection loss peak reaches -17.2db near 5.1GHz, and when the coating thickness is 3mm, its reflection loss peak reaches -35.5db near 3.2GHz. It has good corrosion resistance and high absorbing performance.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present application first uses hydrofluoric acid to modify graphene and then composites it with flaky carbonyl iron to prepare a composite absorbing material. The modified graphene is partially fluorinated to improve the corrosion resistance and environmental weather resistance of the graphene material itself, and the surface of the modified graphene material will carry a large amount of -COOH; and the flaky carbonyl iron will carry a large amount of -NH2 on the surface after being modified by the coupling agent KH-550, which will then better connect with the graphene with a large amount of -COOH on the surface, and finally form a low dielectric fluorinated graphene coating on the surface of the carbonyl iron to significantly improve the corrosion resistance of the carbonyl iron;
[0019] 2. The composite absorbing material prepared by compounding modified graphene with flaky carbonyl iron in this application not only improves the corrosion resistance of carbonyl iron, but also does not affect the absorbing performance of carbonyl iron. The composite material has lower real and imaginary parts of the complex dielectric constant and is more suitable for achieving better impedance matching. When the coating thickness is 3 mm, its reflection loss peak can reach -35.5 dB near 3.2 GHz.
[0020] 3. The preparation process of the composite absorbing material disclosed in the present application is simple, the raw materials used are easy to obtain, the overall preparation cost is effectively controlled, and it is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Small figures ac in the middle are scanning electron microscope (SEM) images of the composite absorbing material prepared in Example 1 at different magnifications;
[0022] Figure 2 Small figures ac in the middle are transmission electron microscope images of the composite absorbing material prepared in Example 1 at different magnifications;
[0023] Figure 3A is the real part curve of the complex magnetic permeability of the composite absorbing material prepared in Example 1;
[0024] Figure 3B is the imaginary part curve of the complex magnetic permeability of the composite absorbing material prepared in Example 1;
[0025] Figure 4A is the real part curve of the complex dielectric constant of the composite absorbing material prepared in Example 1;
[0026] Figure 4B is the imaginary part curve of the complex dielectric constant of the composite absorbing material prepared in Example 1;
[0027] Figure 5 is the reflection loss curve of the composite absorbing material prepared in Example 1 (coating thickness 1 to 4 mm);
[0028] Figure 6 Panels a and b are the appearance photos of the composite absorbing material prepared in Example 1 and the flaky carbonyl iron material as a comparison after a 1000-hour salt spray test. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0030] Example 1
[0031] This embodiment discloses a method for preparing a corrosion-resistant composite wave-absorbing material
[0032] 1) Graphene modification: Weigh 5 g of industrial-grade graphene powder and disperse it in 500 mL of pure water, and ultrasonically disperse it for 2 h to obtain a graphene dispersion; add the dispersion into a hydrothermal reactor lined with polytetrafluoroethylene, add 20 mL of hydrofluoric acid (the mass concentration of hydrofluoric acid is 20%), tighten the hydrothermal reactor to make it airtight, place it in an oven, and keep it warm at 240°C for 10 h. After the reaction is completed, cool it naturally, filter it, and wash the filter cake with pure water 5 times until its pH value reaches neutral.
[0033] 2) Preparation of flaky carbonyl iron powder: Weigh 10 g of carbonyl iron powder and put it into a planetary ball mill, add 500 mL of anhydrous ethanol as a process control agent, add 1000 g of zirconia balls with a diameter of 6 mm as grinding balls (i.e., the ball-to-material ratio is 100:1), ball mill at 800 rpm for 24 hours, then take out the iron powder, put it into a forced air drying oven and dry it at 60°C for 2 hours to obtain a flaky carbonyl iron powder with a diameter-to-thickness ratio of approximately 10:1.
[0034] 3) Preparation of composite absorbing material: 100 g of flaky carbonyl iron powder was dispersed in 200 mL of anhydrous ethanol using a stirrer at 500 rpm, and stirred for 30 min to obtain a CIP dispersion; 0.1 g of silane coupling agent KH-550 and 1 g of distilled water were added dropwise to the CIP dispersion, and the mixture was stirred at 800 rpm for 1 h; 50 g of modified graphene dispersion (prepared by dispersing the modified graphene prepared in step 1) in anhydrous ethanol, with a solid content of 5%) was then added, and the mixture was stirred in an oil bath at 60° C. for 4 h; the mixed dispersion was filtered, and the composite was placed in a vacuum drying oven and vacuum dried at 60° C. for 4 h; the composite material was passed through a 50-mesh sieve and then vacuum sealed for storage.
[0035] In this embodiment, graphene is modified by hydrofluoric acid so that the graphene is partially fluorinated. The fluorinated graphene has excellent physical and chemical properties such as low surface energy, strong hydrophobicity and wide band gap. At the same time, the fluorinated graphene also has unique properties such as high temperature resistance, corrosion resistance, friction resistance, stable chemical properties and excellent lubricity. Carbonyl iron powder is a soft magnetic particle, which is easily magnetized under the action of an external magnetic field. The magnetized particles are easily self-agglomerated, so the pure carbonyl iron powder has poor dispersion uniformity in the dispersion medium. The carbonyl iron powder particles are preliminarily modified by the silane coupling agent KH-550. One end of the coupling agent is hydrolyzed to form Si-O bonds and stably bonded to the carbonyl iron powder particles, and the other end contains a large amount of -NH2. Since graphene will carry a large amount of -COOH on its surface when it is partially fluorinated, the carbonyl iron particles that have been initially modified by the silane coupling agent will theoretically have good compatibility with the fluorinated graphene sheets with a large amount of -COOH on the surface, and can form more chemical bonds, thereby forming a low-dielectric fluorinated graphene coating on the surface of the carbonyl iron, rather than simply compounding the graphene material with the carbonyl iron material, which can further improve the corrosion resistance and environmental weather resistance of the carbonyl iron. The relevant performance has been further verified through subsequent tests.
[0036] Firstly, scanning electron microscopy was used to characterize the microstructure of the experimental samples. Figure 1 As shown in the small picture AC in the middle, it can be seen from the picture that the powder particles are relatively dispersed, and the morphology is a certain regular flake structure; the surface of some spherical carbonyl iron powders and the side and plane surfaces of the flake carbonyl iron powders are coated with graphene. Combined with the low-magnification transmission electron microscopy image of the sample ( Figure 2 ) Further observation revealed that the graphene material was completely coated on the surface of the carbonyl iron powder, indicating that the composite with modified graphene would indeed change the particle distribution state of carbonyl iron, which in turn may significantly affect the absorbing performance of the absorbing material.
[0037] Then the complex magnetic permeability and complex dielectric constant (μ′, μ″, ε′, ε″) of the sample were measured in the frequency range of 1 to 18 GHz, as shown in Figure 3A , 3B , 4A, and 4B.
[0038] from Figure 3A It can be seen that the real part of the complex permeability generally shows a downward trend with the increase of frequency, and the higher the frequency, the more gradual the downward trend becomes. Figure 3B It can be seen that the imaginary part of the complex magnetic permeability shows an upward trend in the range of 1 to 3.8 GHz, a downward trend in the range of 3.8 to 18 GHz, and an obvious magnetic loss peak appears at the frequency point of 3.8 GHz.
[0039] Combination Figure 3A and Figure 3B It can also be seen that the magnetic permeability of the composite absorbing material prepared in this embodiment changes little. This is because the modified graphene forms a complete coating layer on the surface of the carbonyl iron, which has little effect on the complex magnetic permeability of the carbonyl iron powder.
[0040] from Figure 4A It can be seen that in the frequency range of 1 to 18 GHz, due to the dispersion phenomenon, the real part of the complex dielectric constant generally shows a decreasing trend with the increase of frequency, and the decline process is relatively gentle. Figure 4B It can be seen that the imaginary part of the complex dielectric constant decreases with the increase of frequency in the frequency range of 1 to 18 GHz, and it presents a multi-mode resonance curve within the frequency range. Figure 4A and Figure 4B From the perspective of dielectric constant, composite absorbing materials have lower real and imaginary parts of complex dielectric constant, which is suitable for achieving better impedance matching.
[0041] Figure 5 The reflection loss curves are obtained when the material thicknesses are designed by the electromagnetic field transmission line theory formula and are 1, 1.5, 2, 2.5, 3, 3.5, and 4 mm, respectively. It can be clearly seen from the figure that when the material thickness is 2 mm, at the frequency point of 5.1 GHz, the reflection loss extreme value of the composite absorbing material prepared in this embodiment is -17.2 dB; when the material thickness is 3 mm, at the frequency point of 3.2 GHz, the reflection loss extreme value of the composite absorbing material can reach -35.5 dB; the absorbing performance of the composite absorbing material is effectively improved, and the corrosion resistance can also be greatly improved.
[0042] The composite absorbing material and pure carbonyl iron sheet prepared in this example were subjected to a 1000h salt spray test. Figure 6 Compared with the flake carbonyl iron powder not composited with modified graphene, the flake carbonyl iron composited with modified graphene showed no obvious oxidative corrosion after 1000h of salt spray test ( Figure 6 The flake carbonyl iron material showed obvious oxidation and corrosion after 1000h of salt spray test ( Figure 6 (inset in middle b).
[0043] Example 2
[0044] 1) Graphene modification: Weigh 10g of industrial-grade graphene powder and disperse it in 500mL of pure water, and ultrasonically disperse it for 4h to obtain a graphene dispersion; add the dispersion into a hydrothermal reactor lined with polytetrafluoroethylene, and add 15mL of hydrofluoric acid (the mass concentration of hydrofluoric acid is 20%), tighten the hydrothermal reactor to make it airtight, place it in an oven, and keep it at 220°C for 12h. After the reaction is completed, cool it naturally, filter the reaction solution, and wash the filter cake with pure water 5 times until its pH value reaches neutral;
[0045] 2) Preparation of flaky carbonyl iron powder: Weigh 10 g of carbonyl iron powder and put it into a planetary ball mill, add 500 mL of anhydrous ethanol as a process control agent, add 500 g of zirconia balls with a diameter of 3 mm as grinding balls (i.e., the ball-to-material ratio is 50:1), ball mill at 1000 rpm for 36 hours, then take out the iron powder, put it into a forced air drying oven and dry it at 70°C for 1 hour to obtain flaky carbonyl iron powder with a certain diameter-to-thickness ratio.
[0046] 3) Preparation of composite absorbing material: 100 g of flaky carbonyl iron powder was dispersed in 300 mL of ethylene glycol solution using a stirrer at 800 rpm, and stirred for 15 min to obtain a CIP dispersion; 0.2 g of silane coupling agent KH-550 and 2 g of distilled water were added dropwise to the CIP dispersion, and the mixture was stirred at 1000 rpm for 2 h; 100 g of modified graphene dispersion (prepared by dispersing the modified graphene prepared in step 1) in ethylene glycol, with a solid content of 5%) was then added, and the mixture was stirred in an oil bath at 70° C. for 2 h; the mixed dispersion was filtered, and the composite was placed in a vacuum drying oven at 50° C. and vacuum dried for 6 h; the composite material was passed through a 50-mesh sieve and then vacuum sealed for storage.
[0047] Example 3
[0048] 1) Graphene modification: Weigh 15g of industrial-grade graphene powder and disperse it in 1000mL of pure water, and ultrasonically disperse it for 6h to obtain a graphene dispersion; add the dispersion into a hydrothermal reactor lined with polytetrafluoroethylene, add 40mL of hydrofluoric acid (the mass concentration of hydrofluoric acid is 15%), tighten the hydrothermal reactor to make it airtight, place it in an oven, and keep it at 260°C for 10h. After the reaction is completed, cool it naturally, filter it, and wash the filter cake with pure water 5 times until its pH value reaches neutral;
[0049] 2) Preparation of flaky carbonyl iron powder: Weigh 20 g of carbonyl iron powder and put it into a planetary ball mill, add 500 mL of anhydrous ethanol as a process control agent, add 500 g of zirconia balls with a diameter of 6 mm as grinding balls (i.e., the ball-to-material ratio is 25:1), ball mill at 1200 rpm for 16 hours, then take out the iron powder, put it into a forced air drying oven and dry it at 80°C for 1.5 hours to obtain flaky carbonyl iron powder with a certain diameter-to-thickness ratio.
[0050] 3) Preparation of composite absorbing material: 100 g of flaky carbonyl iron powder was dispersed in 400 mL of anhydrous ethanol using a stirrer at 500 rpm, and stirred for 60 min to obtain a CIP dispersion; 0.5 g of silane coupling agent KH-550 and 5 g of distilled water were added dropwise to the CIP dispersion, and the mixture was stirred at 1200 rpm for 4 h; 80 g of modified graphene dispersion (prepared by dispersing the modified graphene prepared in step 1) in anhydrous ethanol, with a solid content of 5%) was then added, and the mixture was stirred in an oil bath at 90° C. for 2 h; the mixed dispersion was filtered, and the composite was placed in a vacuum drying oven at 60° C. and vacuum dried for 6 h; the composite material was passed through an 80-mesh sieve and then vacuum sealed for storage.
[0051] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant composite absorbing material, characterized in that: The steps include: 1) adding hydrofluoric acid to the graphene aqueous dispersion, hydrothermally reacting, cooling, filtering, and washing to neutrality to obtain modified graphene; 2) mixing the carbonyl iron powder with an organic solvent, ball-milling the mixture, and drying the mixture to obtain flaky carbonyl iron powder; 3) Dispersing the flaky carbonyl iron powder in an organic solvent under stirring, adding a coupling agent and water, continuously stirring, then adding the modified graphene dispersion, heating in an oil bath, filtering, and drying to obtain a composite absorbing material.
2. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 1), the graphene concentration in the graphene aqueous dispersion is 0.01-0.1 g / mL, the solid-liquid ratio of graphene to hydrofluoric acid is 1-20 g / 5-60 mL, and the mass concentration of hydrofluoric acid is 10%-48%.
3. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 1), the hydrothermal reaction temperature is 220-280° C. and the insulation time is 4-16 hours.
4. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 2), the organic solvent is anhydrous ethanol, the ball-to-material ratio during ball milling is 20-100:1, the ball milling speed is 800-1200 rpm, and the ball milling time is 12-48 h; the drying temperature is 60-80° C., and the drying time is 0.5-4 h.
5. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 3), the organic solvent is one or more of anhydrous ethanol and ethylene glycol; the coupling agent is KH-550, the mass ratio of flaky carbonyl iron powder, coupling agent and water is 100:0.1-1:1-10, the continuous stirring speed is 800-1200rpm, and the stirring time is 1-4h.
6. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 3), the solid content of the modified graphene dispersion is 3% to 10%, and the mass ratio of the flaky carbonyl iron powder to the modified graphene in the mixed dispersion is 100:2 to 10.
7. The method for preparing a corrosion-resistant composite absorbing material according to claim 1, characterized in that: In step 3), the oil bath temperature is 60-100° C. and the oil bath time is 1-6 h.
8. A corrosion-resistant composite absorbing material, characterized in that: The invention relates to a novel nanostructured carbon foam. The nanostructured carbon foam is prepared according to the preparation method described in any one of claims 1 to 7.
9. The corrosion-resistant composite absorbing material according to claim 8, characterized in that: The composite material is prepared by compounding graphene modified by hydrofluoric acid with flaky carbonyl iron powder modified by a coupling agent. The surface of the modified graphene carries -COOH, and the surface of the modified flaky carbonyl iron powder carries -NH2. The modified flaky carbonyl iron powder is chemically bonded to the graphene with -COOH on its surface through the -NH2 on its surface, and then a low dielectric fluorinated graphene coating layer is formed on the surface of the flaky carbonyl iron, thereby improving the corrosion resistance of the carbonyl iron and the impedance matching performance of the composite material.
10. The corrosion-resistant composite absorbing material according to claim 8, characterized in that: When the coating thickness is 2mm, the reflection loss peak reaches -17.2db near 5.1GHz, and when the coating thickness is 3mm, the reflection loss peak reaches -35.5db near 3.2GHz.
Citation Information
Patent Citations
A method for preparing corrosion-resistant carbonyl iron / graphene composite microwave absorbing material for 5G mobile communication bands
CN109897597B